Viability of probiotic cultures Lactobacillus acidophilus and Bifidobacterium lactis added to the Curd Cheese (Research, Society and Development, 2019)
The present study aimed to evaluate the viability of probiotic cultures in the production of Coalho cheese. Three treatments with three replicates were used: Curd cheese added Lactobacillus acidophilus (T1); Bocal cheese added Bifidobacterium lactis (T2); and traditional Curd cheese, without addition of culture (T3). The cheeses were analyzed for their physico-chemical and sensorial composition every 7 days until the 28th day. Treatment T1 presented a probiotic population count within the allowed by the legislation and there was no significant sensorial differentiation between the others. Therefore, the added Combination Cheese of L. acidophilus presented propitious conditions to be considered a new alternative of probiotic food.